2020
DOI: 10.3390/pr8020236
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Melanogenesis, Antioxidant and Anti-Tyrosinase Activities of Scabiosa columbaria L.

Abstract: Scabiosa columbaria is a plant traditionally used to treat skin ailments, such as scabies, wound bruises, sores and hyperpigmentation. To find a novel skin depigmenting agent, the present study was investigated to determine the possible anti-melanogenesis, antioxidant and anti-tyrosinase effects of methanol extract of S. columbaria leaves. Cytotoxicity towards human dermal fibroblast (MRHF) cells was assessed using the live-cell fluorescence imaging microscopy. The inhibitory effects of the extract on tyrosina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
(18 reference statements)
1
19
0
Order By: Relevance
“…Inhibition of the tyrosinase enzyme was investigated via the dopachrome method as previously described [19], with some modifications. L-DOPA was used as a substrate.…”
Section: Determination Of Tyrosinase Inhibitory Activitymentioning
confidence: 99%
“…Inhibition of the tyrosinase enzyme was investigated via the dopachrome method as previously described [19], with some modifications. L-DOPA was used as a substrate.…”
Section: Determination Of Tyrosinase Inhibitory Activitymentioning
confidence: 99%
“…Chlorogenic and caffeic acids, which are diphenolics have a higher radical scavenging ability than monophenolics (p coumaric acid) ( Rice-Evans et al, 1996 ). Otang-Mbeng and Sagbo (2020) reported that the FRAP test of the leaves of Scabiosa columbaria had high antioxidant activity values due to presence of polyphenolic compounds. Hafsa et al (2009) concluded that extracts (acetonic, ethanolic and aqueous) obtained using different solvents from Scabiosa arenaria Forssk showed high antioxidant activity with different activity tests such as DPPH scavenging capacity (highest inhibition percentages 93.84%), radical cation ABTS .+ scavenging activity (after 5 min from 7.50% to 93.67% for ethanolic extract), TEAC assay (2.25 mM trolox/g extract) and total phenolic content (138.36 mg catechin/ g extract).…”
Section: Discussionmentioning
confidence: 99%
“…Although researches have been carried out to determine the chemical composition and biological activities of Scabiosa columbaria L. at the species and subspecies category ( Horn et al, 2001 , Benli et al, 2008 , Van Vuuren and Naidoo, 2010 , Otang-Mbeng and Sagbo, 2020 , Sagbo et al, 2020 ), no research has yet been carried out to determine the characteristics specified at the variety category.…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic activity of B. asphodeloides on MRHF cells was assessed by the Hoechst 33342/PI dual-staining method [ 17 ]. Cells were seeded in a 96 well-plate at a density of 8000 cells/well using aliquots (100 μ L) and left to attach overnight.…”
Section: Methodsmentioning
confidence: 99%